A Comparative Analysis of Gricean Maxims in Sakura Sakura and Mō Lì Huā - Ucca Diandra Tantra Baswara (JURNAL PENDIDIKAN BAHASA, 2025)
The two traditional songs, Sakura Sakura and Mō Lì Huā, originated from different countries. These traditional songs are often referred to as iconic popular songs that represent two different aspects of beautiful flowers in Japan and China. With the Grice lens on maxims and violated of maxims, it may reveal the hidden structural meaning of these two traditional songs. The objective of this research was to determine 1) How frequently are the Gricean maxims fulfilled and violated in Sakura Sakura? 2) How frequently are the Gricean maxims fulfilled and violated in Mō Lì Huā? The research applied the qualitative method with a comparative analysis. The data collection procedure involved identifying the recognized maxims, assigning those related to them, classifying the responses, and integrating the maxims and violations. The research showed there were six lyrics of Sakura Sakura, Cherry Blossoms, one maxim quality, and one maxim relation. Sakura Sakura has four violations: two violations of quality and two violations of quantity. Meanwhile, Mō Lì Huā, Jasmine Flower has five lyrics, one maxim quantity, and one maxim relation. Mo Lì Huā, three violations, two violations of quality, and one violation of manner.